Utilization of sex-sorted semen in beef cattle - Aubuchon, Kolton Wyatt (Kansas State University, 2022)
Reproduction is one of the most important traits for cattle producers. The continued and consistent production of calves for market and replacement purposes is the backbone of many cattle operations’ economic success. The value of male and female calves can vary greatly depending on the purpose that animal is meant to serve. This difference in value has made the ability to control the gender of a calf crop a topic of great interest. The development of sex-sorted semen has given producers the ability to shift the ratio of male and female offspring within their operation. The relative novelty of sex-sorted semen means there are still improvements being made to the technology and room for further adoption to occur. In the first chapter, a review of the literature encompasses the development of sex-sorted semen, its uses in different industries and operations, and its differences from unsorted semen. Three studies were conducted to evaluate the use of sex-sorted semen in beef cows and heifers. The second chapter describes research evaluating the use of X- and -Y- sorted semen in beef cows and heifers using various estrous synchronization and timing of insemination. The finding of this study further supports existing evidence of the importance of detection of estrus when utilizing sex-sorted semen and also showed the potential for use of Y-sorted semen in terminal mating systems. The third chapter evaluates the use of sex-sorted semen in beef heifers following synchronization using MGA-PG and insemination following heat detection. Results indicate that inseminating at a later time following observation of estrus behavior is advantageous when utilizing sex-sorted semen. The last chapter evaluated the difference between the novel 7&7 Synch and the classic 7-Day CO-Synch+CIDR estrous synchronization protocols following fixed-time AI (FTAI) with Y-sorted semen. Results of this study showed no difference between the 7&7 Synch and the 7-Day CO-Synch+CIDR protocols in the mature cows, but that the 7-Day CO-Synch+CIDR was more effective on two-year-old cows. Results of these studies indicate that sex-sorted semen can be utilized in beef cattle operations and acceptable pregnancy rates can be achieved. Further research is needed to improve the technology.
Keywords: Beef; Cattle; Sex-sorted semen; Sexed-semen